The Effect of Ginger Compress On Reducing The Pain Scale of Gout Sufferers (Literatur Review): The Effect of Ginger Compresses On Reducing The Pain Scale of Gout Sufferers (Literatur Review) - Yani Trihandayani (Badan Riset dan Inovasi Nasional, 2024)
Background: The incidence of gout in the world has reached 335 million people. Uric acid is the result of purine metabolism in the body whose levels should not be excessive. The pain that arises in gout is part of the joints. One of the treatments of pain due to nonpharmacological uric acid is to use traditional remedies such as ginger. Purpose: The purpose of this literature is to analyze the effect of ginger compresses on reducing the pain scale in gout sufferers. Methods: This research method is literature review through the google scholar database (2015-2021), using the keywords: